Integrasi Kurikulum Madrasah Mu’allimin-Mu’allimat Pondok Pesantren Sunan Drajat Lamongan (Implementasi Pasal 17 dan 18, UU No 18 Tahun 2019) - Zainul, Zainul Mushthofa; Aminah, Siti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
In 2007, the President of the Republic of Indonesia issued a government regulation regarding the implementation of religious education which recognized that this type of Islamic education had made a major contribution to national development. The regulation explains that religious education such as pesantren can be managed formally. Following the government regulation, the Minister of Religion then issued a 2014 Ministerial Regulation to officially recognize pesantren as traditional-based education. The regulation allows for the integration of yellow book-based education which allocates 70% or more of the curriculum for Islamic studies and Arabic, while 30% for general subjects. The process of formalizing traditional Islamic education reached its climax with the passing of Law No. 18 of 2019 concerning Islamic boarding schools which was legalized on September 24, 2019. The pesantren system must be modernized and run classrooms under the madrasa system. In contrast, the 2019 law recognizes many aspects of traditional pesantren traditions, including those advocating the study of the yellow book. According to the law, the government is currently responsible for supporting the delivery of traditional pesantren-based education as well as support for public schools and madrasas. One of the Islamic boarding schools that has implemented the pesantren law is the Sunan Drajat Islamic Boarding School. The Islamic boarding school inherited from Sunan Drajat, one of the nine guardians, has since 1994 established the Mu'allimin-Mu'allimat institution whose curriculum has integrated the pesantren curriculum with the general education curriculum